DINAMIKA KEHIDUPAN SOSIAL BUDAYA ETNIS TIONGHOA DALAM BINGKAI KEBIJAKAN ASIMILASI ORDE BARU (1966-1998) - Levia Chessiagi; Wawan Darmawan; Tarunasena Ma'mur (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
TThis research titled “The Dynamics of SocioCulture Life of Chinese Ethnic in Frames of Assimilation Policy by the New Order Government (1966-1998)”. The background why researcher took this problem is due to the interest in the condition of Chinese ethnic and the assimilation policy that applied by New Order Government. The application of assimilation policy has an impact on the limited space of Chinese ethnic lives. The main issue that examined in this research is “How was the New Order Government applied the assimilation policy toward Chinese ethnic in Indonesia specially in socio-culture aspect in 1966-1988?” This problem was examined by using the historical method that divided into four steps: Heuristic, Critic, Interpretation, Historiography. As for the data collection that used is literature studies by examining many literature sources which relevant with the topic. Based on the results, could be explain that First New Order Government applied the assimilation policy influenced by the idea of Chinese figures and made the ide as an official policy to resolve problems of Chinese ethnic that had long been happened in Indonesia. Second, the implementation of assimilation policy was experienced some obstacles and caused some problems on its implementation. Third, assimilation policy in social-culture aspect gave the negative impact that limiting the movement of Chinese ethnic in various areas of life, but gave them the room in economic aspect, assimilation policy was also giving the positive impact in creating multicultural society. The results of this study can be seen that the mutual respects were needed for the creation of harmony between communities in the country.